Facial changes evaluation after rehabilitation treatment in edentulous patients by 3D Stereophotogrammetry - Toyoshima, Guilherme Hideki de Lima (2021)
The need for complete dentures in Brazil is still relevant. And it can be said that the facial profile of the edentulous patient is recomposed using this kind of treatment. There are few objective studies dedicated to characterizing and evaluating the changes brought about by this type of dental prosthetic rehabilitation. An objective way of evaluating these patients is using facial stereophotogrammetry, which makes this assessment possible with precision. Thirty patients were selected who were rehabilitated using double full dentures, 7 men and 23 women. They were submitted to stereophotogrammetry (Vectra H1) in 2 stages: with and without the complete dentures. The images were evaluated using a specific software (Vam Canfield), measuring linear and angular measurements from pre-determined craniometric points before taking the photographs. Both groups were submitted to the paired t-test for statistics, with a test power of 0.80 and a significance level of 0.05. As a result, we obtained a statistically significant difference in 7 of the 13 linear measures and 7 of the 9 angular measures evaluated. We highlight an increase in linear measurements: Sn- Gn (lower third of the face) from 64.568 ± 4.802mm to 66.137 ± 4.6949mm, Ls-Li (lip vermilion height) from 7.770 ± 2.547mm to 10.411 ± 2.070mm and Chesq-Chdir (mouth width) from 44.16 ± 5.66mm to 49.66 ± 4.40mm. As well as the reduction in Sn-Ls (nasal filter height) from 18.084 ± 3.221mm to 17.525 ± 3.109mm. In the case of angular measurements, we observed an increase in Sn-St-Pg (lower facial convexity) from 157.01 ± 12.46mm to 166.52 ± 9.00mm and the reduction in the Prn-Sn-Ls angles (angle nasolabial) from 131.61 ± 11.63mm to 124.46 ± 10.75mm and Godir-Pg-Goesq (jaw convexity) from 76.285 ± 4.982mm to 75.463 ± 5.116mm. It was possible to observe relevant changes in the facial profile of newly rehabilitated patients with double full dentures, with patterns such as an increase in the lower facial third, greater expression of lips, support for the upper and lower lips, and changes in facial convexity, these being important characteristics to be determined and followed by the dentist during the prosthetic treatment stages.